2010
DOI: 10.1155/2011/394108
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Alkyl Chain Cation‐Solvent Interactions on Water Structure in 1,3‐Butanediol‐Water Mixture by Apparent Molar Volume Data

Abstract: The densities of 1,3-butanediol-water mixtures and some tetraalkylammonium iodide salt solutions in these solvent mixtures at different concentrations (0.02 M-0.14 M) have been determined at 298.15 K using magnetic float densitometer technique. Then apparent molar volumes ΦVof the electrolytes in above solvent mixtures were calculated. The apparent molar volumes of transfer ∆ΦV° (tr) were also calculated and the ion-ion / ion- solvent interactions are then discussed on the basis of changes in the Masson's slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This result confirms that formation of cavities inside the enhanced water structure and R 4 N + ions are accommodated in the cavities so formed [19]. RN Pathak et al reported various observations by taking aqueous and non-aqueous binary solvent mixture, adding R 4 NI salts and showing the validity of Frank's hypothesis for salts solutions [20]. Their observations were confirmed that such solute -solvent hating effect is still there and structure of any of the binary solvents is affected by the ion -solvent interactions.…”
Section: Introductionsupporting
confidence: 76%
“…This result confirms that formation of cavities inside the enhanced water structure and R 4 N + ions are accommodated in the cavities so formed [19]. RN Pathak et al reported various observations by taking aqueous and non-aqueous binary solvent mixture, adding R 4 NI salts and showing the validity of Frank's hypothesis for salts solutions [20]. Their observations were confirmed that such solute -solvent hating effect is still there and structure of any of the binary solvents is affected by the ion -solvent interactions.…”
Section: Introductionsupporting
confidence: 76%
“…The apparent molar volume (ϕ v ) of the electrolytes in solution is given by Masson's equation 8 namely,…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…14−16 The properties of tetraalkylammonium bromides in water−glycol mixed solvents have only been studied for water−pentane-1,5-diol solutions. 17 This is why we decided to study the effects of tetraalkylammonium bromides as additives to water−propane-1,2-diol mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…It seems obvious that the properties of the liquids are determined by the structural factors arising from the solute–solvent interactions controlling molar volumes, compressibilities, as well as expansibilities of the solution. Structure and thermodynamic properties of tetraalkylammonium bromides in single solvent systems in water as well as in nonaqueous solvents have been extensively studied and the obtained parameters have been discussed in terms intermolecular interactions. Information concerning the respective salt solutions in mixed solvent systems is much more scarce. The properties of tetraalkylammonium bromides in water–glycol mixed solvents have only been studied for water–pentane-1,5-diol solutions …”
Section: Introductionmentioning
confidence: 99%